Удосконалення технології подрібнення магнетитових кварцитів на гірничому підприємстві - Сокур, Микола Іванович; Воробйов, В. В.; Аргат, Роман Григорович; Білецький, Володимир Стефанович; Пузир, Руслан Григорович (Кременчуцький національний університет ім. Михайла Остроградського, 2020)
Показано, що одним з недоліків проектної технологічної схеми самоподрібнення є застосування в ній спіральних класифікаторів, які є дорогим, металоємним і енергоємним устаткуванням, що вимагає значних експлуатаційних витрат на підтримку працездатності. Для підвищення ефективності процесів подрібнення і класифікації, спрощення технологічної схеми, зниження капітальних і експлуатаційних витрат, підвищення якості продукції запропоновано оснастити рудногалечний млин МРГ-40-75 новою конструкцією класифікуючої бутари з еластомерною просіваючою поверхнею. Відповідно до цього було проведено ряд експериментальних випробувань в режимі порівняння технологічних показників роботи млина з двоситною бутарою з класифікатором і без класифікатора. Що дало змогу зробити впровадження цієї науково-технічної розробки у гірниче підприємство. Це дозволило істотно знизити капітальні і експлуатаційні витрати на процеси подрібнення і класифікації, зменшити простої секцій фабрики на монтажах і замінах класифікаторів, значно скоротити питомі витрати електроенергії за рахунок виключення потужного електроприводу класифікатора, а також поліпшити санітарногігієнічні умови на технологічних секціях збагачувальної фабрики.

Purpose. Improvement of the circuit diagram of the apparatus of the RZF-2 concentrator of the Ingulets GZK by replacing energy-intensive and less reliable apparatus with energy-saving and more efficient ones. One of the disadvantages of the project technological scheme of self-grinding is the use of spiral classifiers, which are expensive, metalintensive and energy-intensive equipment that requires significant operating costs to maintain efficiency. Wear and breakage of spirals of classifiers led to long downtimes of technological sections of grinding and classification. Replacing classifiers and their components with new ones has become a difficult problem, as the manufacturer is located in Russia. Methodology. The main tasks of the tests were to establish the efficiency and reliability of the new design of the butar, to determine the technological parameters of its operation and the possibility of improving product quality. Comparison of technological indicators of operation with two-sieve butar and with the classifier, determination of possibility of exclusion of the classifier from the technological scheme as energy-intensive, unreliable and inefficient classifying device, development of measures to improve the design of two-sieve butar, contributes to increasing the efficiency of both the butar itself and the technological scheme as a whole. During the tests, the following samples were taken: initial ore, pebbles, sub-sieve product, mill drains, classifiers, hydrocyclones, power supply and magnetic products of magnetic separation, tailings and scrap. When processing, the test data were determined by productivity, power, particle size composition of products, pulp density, solids content, total and magnetic iron content in industrial products and concentrate, the content of the finished class in industrial products and concentrate. Results. From the analysis of test results, it follows that with the use of two-sieve butar the content of the finished class (minus 0.05 mm) in the subsieve product butary increased compared with the classifier in the first experiment. When using two-sieve butar, the amount of scrap significantly reduces. The quality of the concentrate (mass fraction of iron in the concentrate) with the use of two-sieve butar increased by 0.1%, the loss of iron in the tailings decreased. Practical value. It is proposed to change the scheme of circuits of devices of the concentrator of Ingulets GZK having excluded from it the spiral classifier, which was carried out on a number of technological sections of the concentrator. Prolonged technological tests have confirmed the effectiveness of the proposed engineering solution. The introduction of this scientific and technical development has significantly reduced capital and operating costs of the processes of grinding and classification, to reduce downtime of sections of the factory on installations and replacements of classifiers. It has also enabled to reduce considerably specific expenses of the electric power due to elimination of the powerful electric drive of the classifier, and also to improve sanitary and hygienic conditions at technological sections of the concentrator.
Improving the technology of grinding magnetite quartzites at the mining enterprise
Keywords: бутара; класифікатор; млин; подрібнення; еластомірна поверхня; butar; classifier; mill; grinding; elastomeric surface